Synthesis and in vitro biological evaluation of 2,6,9-trisubstituted purines targeting multiple cyclin-dependent kinases - Zatloukal, Marek; Jorda, Radek; Gucký, Tomáš; Řezníčková, Eva; Voller, Jiří; Pospíšil, Tomáš; Malínková, Veronika; Adamcová, Helena; Kryštof, Vladimír; Strnad, Miroslav (European journal of medicinal chemistry, 2013)
Several inhibitors of cyclin-dependent kinases (CDKs), including the 2,6,9-trisubstituted purine derivative roscovitine, are currently being evaluated in clinical trials as potential anticancer drugs. Here, we describe a new series of roscovitine derivatives that show increased potency in vitro. The series was tested for cytotoxicity against six cancer cell lines and for inhibition of CDKs. For series bearing 2-(hydroxyalkylamino) moiety, cytotoxic potency strongly correlated with anti-CDK2 activity. Importantly, structural changes that increase biochemical and anticancer activities of these compounds also increase elimination half-life. The most potent compounds were investigated further to assess their ability to influence cell cycle progression, p53-regulated transcription and apoptosis. All the observed biological effects were consistent with inhibition of CDKs involved in the regulation of cell cycle and transcription.
Keywords: Dose-Response Relationship, Drug; vztah mezi dávkou a účinkem léčiva; Models, Molecular; apoptóza; Protein Kinase Inhibitors; K562 Cells; Drug Screening Assays, Antitumor; cyklin-dependentní kinasy; screeningové testy protinádorových léčiv; HCT116 buňky; Cell Proliferation; HCT116 Cells; Antineoplastic Agents; buňky K562; molekulární modely; protinádorové látky; vztahy mezi strukturou a aktivitou; Humans; Molecular Structure; Purines; Cyclin-Dependent Kinases; puriny; molekulární struktura; proliferace buněk; inhibitory proteinkinas; Structure-Activity Relationship; lidé; Apoptosis